State-private Partnership in Development of Regional Air Transportation Services - D V Plamadiala (RUDN Journal of Economics, 2009)
The article is about state-private partnership in Russian Federation and the possibility of its implementation in the development of air transportation in Russia. The article concerns the idea of state-private partnership and are given its main characteristics and forms. Thereafter carried out common analysis of the status of air transportation industry in Siberia Federal region and determined the main current problems in this field. In the final part of the article considered measures, which are necessary to be admitted by the state bodies in order to develop airport infrastructure and also the possibility of application in this field the facilities of state-private partnership.